A mutation in cnot8, component of the Ccr4-not complex regulating transcript stability, affects expression levels of developmental regulators and reveals a role of Fgf3 in development of caudal hypothalamic dopaminergic neurons. - Peter Koch; Heiko B Löhr; Wolfgang Driever (PLoS ONE, 2014)
While regulation of the activity of developmental control genes at the transcriptional level as well as by specific miRNA-based degradation are intensively studied, little is known whether general cellular mechanisms controlling mRNA decay may contribute to differential stability of mRNAs of developmental control genes. Here, we investigate whether a mutation in the deadenylation dependent mRNA decay pathway may reveal differential effects on developmental mechanisms, using dopaminergic differentiation in the zebrafish brain as model system. In a zebrafish genetic screen aimed at identifying genes controlling dopaminergic neuron development we isolated the m1061 mutation that selectively caused increased dopaminergic differentiation in the caudal hypothalamus, while other dopaminergic groups were not affected. Positional cloning revealed that m1061 causes a premature stop codon in the cnot8 open reading frame. Cnot8 is a component of the Ccr4-Not complex and displays deadenylase activity, which is required for removal of the poly (A) tail in bulk mRNA turnover. Analyses of expression of developmental regulators indicate that loss of Cnot8 activity results in increased mRNA in situ hybridization signal levels for a subset of developmental control genes. We show that in the area of caudal hypothalamic dopaminergic differentiation, mRNA levels for several components of the FGF signaling pathway, including Fgf3, FGF receptors, and FGF target genes, are increased. Pharmacological inhibition of FGF signaling or a mutation in the fgf3 gene can compensate the gain of caudal hypothalamic dopaminergic neurons in cnot8m1061 mutants, indicating a role for Fgf3 in control of development of this dopaminergic population. The cnot8m1061 mutant phenotype provides an in vivo system to study roles of the Cnot8 deadenylase component of the mRNA decay pathway in vertebrate development. Our data indicate that attenuation of Cnot8 activity differentially affects mRNA levels of developmental control genes.